2014
DOI: 10.1248/bpb.b13-00672
|View full text |Cite
|
Sign up to set email alerts
|

Developing Population Pharmacokinetic Parameters for High-Dose Methotrexate Therapy: Implication of Correlations among Developed Parameters for Individual Parameter Estimation Using the Bayesian Least-Squares Method

Abstract: Bayesian estimation enables the individual pharmacokinetic parameters of the medication administrated to be estimated using only a few blood concentrations. Due to wide inter-individual variability in the pharmacokinetics of methotrexate (MTX), the concentration of MTX needs to be frequently determined during high-dose MTX therapy in order to prevent toxic adverse events. To apply the benefits of Bayesian estimation to cases treated with this therapy, we attempted to develop an estimation method using the Baye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
2
6
0
Order By: Relevance
“…A two-compartment model best characterized the PK of MTX in the 71 infants in our study, which is consistent with previous reports of high-dose MTX in both children and adults [46,48,[50][51][52][53][54][55][56][57]. Our model applied theory based allometry to scale CL and volume of distribution parameters to a standard weight of 70 kg [17,58].…”
Section: Discussionsupporting
confidence: 88%
“…A two-compartment model best characterized the PK of MTX in the 71 infants in our study, which is consistent with previous reports of high-dose MTX in both children and adults [46,48,[50][51][52][53][54][55][56][57]. Our model applied theory based allometry to scale CL and volume of distribution parameters to a standard weight of 70 kg [17,58].…”
Section: Discussionsupporting
confidence: 88%
“…The previous population PK models suggested that a list of covariates [e.g., age (Aumente et al, 2006;Thompson et al, 2007;Colom et al, 2009), body weight (Aumente et al, 2006;Colom et al, 2009), renal function (Dupuis et al, 2008;Fukuhara et al, 2008;Mao et al, 2014), and polymorphisms of transporters (Kim et al, 2012;Liu et al, 2017)] were related to MTX PK exposure. Unlike the previously published population PK models using the two-compartment disposition model (Wall et al, 2000;Aumente et al, 2006;Faltaos et al, 2006;Piard et al, 2007;Min et al, 2009;Buitenkamp et al, 2010;Jönsson et al, 2011;Watanabe et al, 2014;Beechinor et al, 2019), the current study based on 311 pediatric patients enabled to fit the MTX concentration-time data by using a three-compartment disposition model. The final model demonstrated that the MTX clearance estimate in a typical child with a body weight of 19 kg was 6.9 L/h.…”
Section: Discussionmentioning
confidence: 99%
“…28 Base Model Development Current literature and investigations of the pharmacokinetic profiles suggest that a 2-compartment model sufficiently describes the pharmacokinetics of highdose methotrexate, so it was chosen as the base model. [32][33][34][35][36][37][38][39][40][41][42][43][44] Interindividual variabilities in pharmacokinetic parameters, namely clearance, central volume, intercompartmental clearance, peripheral volume, and interoccasion variability in clearance were assumed to follow log-normal distributions. Residual variability was described using the exponential error model.…”
Section: Statistical Softwarementioning
confidence: 99%